PERANAN DESAIN PARIWARA (IKLAN) DI ERA GLOBALISASI - Sugiharjanto, Asto Adi (KEMADHA, 2012)
Today, the term often heard of Visual Communication Design , in our daily lives. Actually, Visual Communication Design is the development of advertising art and graphic design. Visual Communication Design is a sense of visual design language of the disclosure of ideas or messages conveyed through visual forms to the recipient (target audience). Among them is a form of visual images, symbols, symbol, color, illustration and art of writing (typography). The process of delivering visual messages will be delivered to audience with communicative, creative, innovative, effective, and efficient through various forms of media for specific purposes.